2017
DOI: 10.1080/0284186x.2017.1400683
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in different states of breast cancer – comparing different instruments

Abstract: Different HRQoL instruments produce notably different HRQoL scores. The EQ-5D has a pronounced ceiling effect. Pain and fatigue are the most common symptoms associated with poor HRQoL in all disease states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 22 publications
2
46
1
4
Order By: Relevance
“…The observation that QoL can also be of assistance in guiding these decisions is interesting and should be further investigated in prospective studies. Previous real-world studies among breast cancer patients using the EQ-5D report similar to slightly higher utility scores (median ranging from 0.64-0.82) [19,20,22,24,26,42,43] compared to our median (0.69). These differences in utility scores can partly be explained by the fact that most of these studies [22,24,26,43] only included patients that were actively treated for their disease, leaving out the more vulnerable patients receiving supportive care.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The observation that QoL can also be of assistance in guiding these decisions is interesting and should be further investigated in prospective studies. Previous real-world studies among breast cancer patients using the EQ-5D report similar to slightly higher utility scores (median ranging from 0.64-0.82) [19,20,22,24,26,42,43] compared to our median (0.69). These differences in utility scores can partly be explained by the fact that most of these studies [22,24,26,43] only included patients that were actively treated for their disease, leaving out the more vulnerable patients receiving supportive care.…”
Section: Discussionsupporting
confidence: 73%
“…These differences in utility scores can partly be explained by the fact that most of these studies [22,24,26,43] only included patients that were actively treated for their disease, leaving out the more vulnerable patients receiving supportive care. Additionally, the majority of these real-world studies [19,20,24,42] also included patients with early breast cancer for which it can be expected that the QoL will be better due to less disease-related symptom burden. Furthermore, the mean age of patients within these trials varied, where studies with a lower mean age generally reported better utility scores; e.g., the study by Kim et al reported a mean utility of 0.82 in a population with a median age of 49.3 years [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Rautalin et al found that the mean 15D HRQoL score after treatment of breast cancer is 0.91. 25 The present study found relatively similar results of mean 15D score of 0.88 among patients who underwent chest wall resection and reconstruction due to malignancy.…”
Section: Discussionsupporting
confidence: 78%
“…Although the EORTC QLQ-30 was speci cally developed for cancer patients [27,28], past studies [29] have used it to compare the QOL between cancer and non-cancer patients. Given the complexities of low literacy levels and prevalence of non-written dialects, translating the EORTC QLQ-C30 to Dzongkha, the national language, was not feasible.…”
Section: Survey Instrumentmentioning
confidence: 99%